Demonstrating the suitability of canola residue biomass to biofuel conversion via pyrolysis through reaction kinetics, thermodynamics and evolved gas analyses. (May 2019) - Tahir, Mudassir Hussain; Çakman, Gülce; Goldfarb, Jillian L.; Topcu, Yildiray; Naqvi, Salman Raza; Ceylan, Selim
Graphical abstract: Highlights: Canola oil factory residue was investigated as potential pyrolysis feedstock. Residue has higher volatile matter, lower moisture content than other biomasses. Distributed activation energy model applied to canola residue pyrolysis. Evolved gas analysis showed CO2 emission increased with temperature. Thermodynamic and kinetics analysis suggested pyrolysis optimized ∼450 °C. Abstract: The identification of biomasses for pyrolytic conversion to biofuels depends on many factors, including: moisture content, elemental and volatile matter composition, thermo-kinetic parameters, and evolved gases. The present work illustrates how canola residue may be a suitable biofuel feedstock for low-temperature (<450 °C) slow pyrolysis with energetically favorable conversions of up to 70 wt% of volatile matter. Beyond this point, thermo-kinetic parameters and activation energies, which increase from 154.3 to 400 kJ/mol from 65 to 80% conversion, suggest that the energy required to initiate conversion is thermodynamically unfavorable. This is likely due to its higher elemental carbon content than similar residues, leading to enhanced carbonization rather than devolatilization at higher temperatures. Evolved gas analysis supports limiting pyrolysis temperature; ethanol and methane conversions are maximized below 500 °C with ∼6% water content. Carbon dioxide is the dominant evolved gas beyond this temperature.